Influence of patient characteristics on duration of seclusion/restrain in acute psychiatric settings in Japan. Issue 6 (13th August 2013) - Noda, Toshie; Sugiyama, Naoya; Sato, Makiko; Ito, Hiroto; Sailas, Eila; Putkonen, Hanna; Kontio, Raija; Joffe, Grigori
Abstract : Aim: The aim of this study was to investigate the current state of duration of seclusion/restraint in acute psychiatric settings in Japan and the effect of patient characteristics on duration of seclusion/restraint. Methods: During an 8‐month period starting from November 2008, duration of seclusion/restraint and patient characteristics were investigated in 694 psychiatric inpatients who experienced seclusion/restraint in three emergency and three acute wards at four psychiatric hospitals. Reasons for starting seclusion/restraint were also assessed. Analysis was performed using generalized linear models, with the duration of seclusion/restraint as the dependent variable and patient characteristics and reasons for starting seclusion/restraint as independent variables. Results: Of the patients secluded/restrained, 58.6% had a primary diagnosis of schizophrenia (F20–F29) and a large proportion (37.9%) were secluded/restrained due to hurting others. Median hours ofseclusion/restraint were 204 and 82 h, respectively. The duration of seclusion was longer for patients with F20–F29 than those with disorders due to psychoactive substance use (F10–F19) or other diagnoses (F40–F99), and when the reason was danger of hurting others. In contrast, the duration of restraint in female patients and in patients with F10–F19 diagnosis was shorter. Conclusion: The duration of seclusion/restraint at acute psychiatric care wards in Japan are much longer than those reported by previous overseas studies. Although Japanese structure issues such as more patients per ward and a lower ratio of nurses need to be considered, skills for dealing with patients with primary diagnosis of F20–F29 secluded due to danger posed to others should be improved.